The European Fund for Sustainable Development: changing the game? - Erik Lundsgaarde (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
This discussion paper analyses the European Fund for Sustainable Development (EFSD) by reviewing its main features, outlining key debates surrounding its establishment and exploring the fund's prospects at the country level with illustrations from Ghana and Senegal. The paper builds on desk-based analysis and interviews with stakeholders involved in the negotiations leading to the fund's creation. As an example of a blended finance approach, a key goal of the EFSD is to use official development assistance (ODA) resources to stimulate lending and facilitate increased public and private investment. A core innovative element of the EFSD is the guarantee mechanism at its heart. The guarantee is expected to enable counterpart organisations to mobilise investment in riskier areas, in particular in fragile and low-income settings where EU blended finance has, to date, had limited reach. The European Commission estimates that an initial EU contribution to the EFSD of EUR 3.35 billion will generate additional public and private investment on the order of EUR 44 billion. However, the novelty of the guarantee facility also means that it is untested, leaving uncertainty about its consequences for resource mobilisation. Against the backdrop of high expectations for the fund, the paper reviews assessments of previous EU blending efforts, outlines the novel elements of the EFSD and discusses areas of contention in the process leading to the fund's creation. The EFSD builds on a decade of EU experience with blended finance and provides a common umbrella for the continuation of two regional blending facilities supporting investment in Africa and the European Neighbourhood. The fund's creation reflects an extension of ideas from the Investment Plan for Europe to the field of external relations and the political imperative for the EU to support long-term actions addressing migration challenges. The multitude of objectives the EFSD intends to promote reflect high expectations for what it can achieve. Although contributing to the EU's migration management agenda is a key stated aim of the fund, it is unclear how this objective will influence funding priorities. Investment priorities in areas such as the development of renewable energy, transport and ICT infrastructure as well as support for private-sector development are similar to thematic emphases in other EU blending facilities. The fund's structure will expand the role of the European Commission's Directorate-General for International Cooperation and Development in blended finance, and enable the European Parliament to assume an oversight role. The role of the European Investment Bank in the EFSD is less prominent than it had desired, though it will still be significant. The fund's implementation will depend largely on development finance institutions that have already been privileged partners in EU blending, while seeking to diversify the field of involved counterpart organisations. The debate surrounding the establishment of the EFSD highlighted differences in views among EU member states in their understanding of how development cooperation should support efforts to limit migration. The Parliament advocated for a stronger linkage between the fund's objectives and the SDG and development effectiveness agendas, and encouraged a stronger commitment to climate action – a position only partially reflected in the regulation establishing the fund. Another area of contention related to the division of institutional responsibilities between the European Commission and the European Investment Bank in the fund's overall management, which was resolved in favour of the Commission. External evaluations of previous EU blending activities, as well as a report from the European Court of Auditors, have noted challenges in demonstrating the added value or additionality of blended finance. To date, EU blended finance has primarily served to leverage funding from public development banks rather than private investors. These reports have examined added value from different perspectives, including its ability to accomplish objectives beyond what other development cooperation instruments can achieve, its potential to fill a gap where commercial financing solutions are not available or its complementarity with domestic financing sources in partner countries. As EFSD implementation moves forward, the clarification and communication of the advantages or disadvantages of the fund's approach – in comparison to other alternatives – will be critical in situating the contribution of the fund to European development cooperation and the broader development agenda it aims to advance.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Entwicklungsfinanzierung und öffentliche Finanzen